2021
DOI: 10.3389/fphar.2021.666776
|View full text |Cite
|
Sign up to set email alerts
|

Classes of Drugs that Mitigate Radiation Syndromes

Abstract: We previously reported several vignettes on types and classes of drugs able to mitigate acute and, in at least one case, late radiation syndromes in mice. Most of these had emerged from high throughput screening (HTS) of bioactive and chemical drug libraries using ionizing radiation-induced lymphocytic apoptosis as a readout. Here we report the full analysis of the HTS screen of libraries with 85,000 small molecule chemicals that identified 220 “hits.” Most of these hits could be allocated by maximal common su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 90 publications
(129 reference statements)
0
6
0
Order By: Relevance
“…Previously, we reported on survival of WT and Nrf2–/– gnotobiotic mice given a range of WBI doses where we performed the appropriate SAS probit analysis for radiation dose-related lethality. We found that the LD50/30 for hematopoietic acute radiation syndrome (hARS) between day 10–30 was reduced to 7.0 Gy in Nrf2–/– , as opposed to 8.2 Gy for WT controls [ 46 ]. These data allowed us to give isoeffective survival WBI doses to WT and Nrf2–/– mice and test if the activity of one of our most powerful 4-nitrophenylsulfonamide hARS mitigators, BCN512, [ 46 ] was Nrf2-dependent.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, we reported on survival of WT and Nrf2–/– gnotobiotic mice given a range of WBI doses where we performed the appropriate SAS probit analysis for radiation dose-related lethality. We found that the LD50/30 for hematopoietic acute radiation syndrome (hARS) between day 10–30 was reduced to 7.0 Gy in Nrf2–/– , as opposed to 8.2 Gy for WT controls [ 46 ]. These data allowed us to give isoeffective survival WBI doses to WT and Nrf2–/– mice and test if the activity of one of our most powerful 4-nitrophenylsulfonamide hARS mitigators, BCN512, [ 46 ] was Nrf2-dependent.…”
Section: Resultsmentioning
confidence: 99%
“…We found that the LD50/30 for hematopoietic acute radiation syndrome (hARS) between day 10–30 was reduced to 7.0 Gy in Nrf2–/– , as opposed to 8.2 Gy for WT controls [ 46 ]. These data allowed us to give isoeffective survival WBI doses to WT and Nrf2–/– mice and test if the activity of one of our most powerful 4-nitrophenylsulfonamide hARS mitigators, BCN512, [ 46 ] was Nrf2-dependent. BCN512 was inactive in Nrf2–/– mice, even though they were given lower WBI doses, while it almost completely protected WT mice from hARS lethality when given daily for 5 days starting 24 h after WBI ( Figure 1 D).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The hematopoietic system, consisting of highly proliferative stem cells, stands out as one of the most susceptible organ to radiation-induced injury [ 47 ]. In established animal models for TBI, four FDA-approved drugs targeting the hematopoietic system–Neupogen, Neulasta, Leukine, and Nplate (Romiplostim)-have demonstrated efficacy in increasing HSPCs in irradiated animals [ 2 , 48 50 ]. However, their activity regulating the BM microenvironment for HSPC regeneration remains unexplored.…”
Section: Discussionmentioning
confidence: 99%